PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA MASA PANDEMI COVID -19 DI WEDDING CRAFTING “RUMAH MAHAR SITUBONDO TAHUN 2021 - Ayu Nur Arifatus Sa'diyah; Ahmad Hafas Rasyidi; Lisma Dian Kartika (Growth, 2021)
Satisfaction is an assessment of the characteristics or features of a product, service, or product itself, which provides a level of consumer pleasure related to meeting consumption needs. This study aims to determine the effect of service quality on consumer satisfaction during the COVID-19 pandemic at Wedding Crafting Rumah Mahar Situbondo in 2021. This study uses Ex Post Facto research. The population in this study is the consumer of the Mahar House, the technique of determining respondents is using accidental sampling. Data collection in this study was carried out using observation, questionnaires, and documentation and then analyzed by Chi Square Test. From the results of data analysis obtained by using the Chi Square test analysis formula produces rhit of 14.394 rhit. And at the 5% significance level, the rtab price was 3.841, meaning that the rhit price was 9.393 > the rtab price was 3.841. So it can be concluded that there is an influence of service quality on consumer satisfaction during the COVID-19 pandemic at the Wedding Crafting of Rumah Mahar Situbondo in 2021. The results of the analysis using the contingency coefficient formula (KK) obtained a correlation coefficient value of 0.43. After consulting with the interpretation table above, the value of 0.43 lies between ± 0.41 to ± 0.60, so the level of correlation between the effect of service quality on customer satisfaction is a moderate correlation.